Digitization And Prediction Of The Number Of Tourist Visits In The Bali Province - Made Ika Prastyadewi; I Gusti Lanang Putu Tantra; Putu Yusi Pramandari (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The development of information technology forces all sectors to develop and adapt. It is the same with the tourism sector in Bali which is starting to experience a fairly rapid development of technology adoption. This research aims to (1) explore the role of social media and online travel applications in current Bali tourism and (2) predict the number of foreign tourist visits to Bali Province. This study uses a quantitative approach using the province of Bali as the research location, considering that Bali is one of the leading tourism destinations in Indonesia. The results of the analysis show that the use of information technology, especially social media, makes it easier for tourists to access information related to tourist destinations. with existing developments, it is predicted that there will continue to be an increase in the number of tourist visits every year. This must be followed by the development of the tourism supporting sector and the improvement of all related facilities. In addition, health and safety issues must be a top priority.